Variation and security enhancement of block ciphers by embedding. (17th February 2019) - Shahapure, Shravani; Sule, Virendra; Daruwala, R. D.
Abstract: This paper proposes a method of embedding block cipher algorithms in a new algorithm in order to create variations and improving security of the original algorithm. The method is concretely explained for embedding AES128 block cipher. In practice there is often a need to develop a bank of secure cipher algorithms in short time. Designing such algorithms from first principles is a very long drawn process. The embedding method allows creating a family of ciphers which have an upgraded level of security over a chosen original algorithm and have the same key length with an option to extend the key length. The embedding method is chosen such that the efficiency of operation of the new algorithm is kept close to that of the original algorithm.